Dying alone due to COVID-19 : do the needs of the many outweigh the rights of the few—or the one? - Capozzo, Alejandra (Frontiers Media, 2021)
The COVID-19 pandemic, caused by infection with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has been striking the world since it was first identified in December 2019 in China. The World Health Organization (WHO) declared the outbreak a “public health emergency of international concern” on January 30th, 2020, and recognized its pandemic status on March 11th. The pandemic has caused universal psychosocial impact (1) and global economic disruption. Discourse and measures have been discussed focused on lockdown strategies, healthcare policies (2), application of emerging treatments, accelerated clinical trials, among others. Management guidelines are continuously updated based on emerging findings (3). However, as the disease spreads through a community, suffering deepens due to strict procedures that, arguably, may be questioned from an ethical standpoint. The pandemic has sufficiently disrupted and impaired people’s livelihood worldwide, and every effort to prevent any additional suffering must be made.